INCREASED EFFICIENCY AND RELIABILITY OF MAINTANANCE OF MASS PASSENGER FLOW WITH THE REGULAR ROUTE NETWORK OF CITY TRANSPORT - Valery KURGANOV; Mikhail GRYAZNOV; Kirill DAVYDOV; Liliya POLYAKOVA (Scientific Journal of Silesian University of Technology. Series Transport)
This study is aimed at improving the methods of carriage of passengers by urban transport to improve its reliability and efficiency. It can be achieved by forming back-up bus routes within the existing regular route network for servicing mass passenger-flows. This study theoretically substantiates the impact of back-up bus routes in the current regular route network on the reliability and efficiency of the transport process. Mathematical models of reservation of regular route network and the assessment of the reliability of passenger transport using different reservation schemes are suggested. Methodological recommendations on the formation of passenger traffic on back-up bus routes and cost reduction on its maintenance, by managing the route speed depending on the loading of the city road network, have been developed. Technical and economic evaluation was conducted to the developed methodological toolkit.